Report of a Working Group on Fibre Crops (Flax and Hemp): Second meeting, 7-9 July 2010, Šumperk – Velké Losiny, Czech Republic - Pavelek, M.; Lipman, E.; Bioversity International; European Cooperative Programme for Plant Genetic Resources (2011)
The Second meeting of the ECPGR Working Group on Fibre Crops (Flax and Hemp) was held on 7-9 July 2010 in Velké Losiny, near Šumperk, Czech Republic. Participants from Czech Republic, Italy, Latvia, Portugal, Russian Federation and Turkey reported on the status of their national collections of flax and hemp and discussed the progress made by the Working Group since the first meeting in 2006. A workplan was developed for the updating and development of the International Flax Database (managed by AGRITEC, Czech Republic) and of the Hemp Database (managed by CRA-CIN, Italy).Preliminary recommendations were made for the implementation of AEGIS (A European Genebank Integrated System) by the Fibre Crops Working Group.